Love + work : how to find what you love, love what you do, and do it for the rest of your life - Buckingham, Marcus (Ascent Audio, 2022)
Love has been driven out of our workplaces. How do we get it back in? We're in the middle of an epidemic of stress and anxiety. Average life expectancy in the US is down. At work, less than sixteen percent of us are fully engaged. In many high-stress jobs such as distribution centers, emergency room nursing, and teaching, incidences of PTSD are higher than veterans returning from war zones. We are getting something terribly wrong. Our workplaces fail utterly to provide for or capitalize on one of our most basic human needs: our need for love. As Marcus Buckingham shows in this eye-opening, uplifting book, love is an energy, and it must flow. It demands expression-and that expression is "work." There's no learning without love, no innovation, no service, no sustainable growth. Love and work are inextricable. Buckingham first starkly highlights the contours of our loveless work lives and explains how we got here. Next, he relates how we all develop best in response to another human being. What does a great work relationship look like when the other person is cued to your loves? Finally, he shows how you can weave love back into the world of work, and how to make this a discipline for the rest of your life. Love + Work powerfully shows why love must come first at work, and how we can make this happen